Assessment of Bacterial Contamination of Fish from Aquaculture Sources and Its Public Health Implications in Abakaliki, Ebonyi State, Nigeria - A. C. Nwuzo; P. C. Igwe; U. C. Aniokete; O. L. Nomeh; E. C. Nwojiji; L. O. Chukwuemeka-Odi; J. Ugwu; U. A. Okpokwu; E. F. Nwadum; J. N. Agbom; N. R. Nwokporo (Journal of Applied Sciences and Environmental Management)
The objective of this paper was assessment of bacterial contamination of fish from aquaculture sources and its public health implications in Abakaliki, Ebonyi state, Nigeria using appropriate standard procedures. .Colony enumeration of bacteria isolates from fish harvested in Abakaliki revealed a high Bacteria count of 6.5 x 10-4cfu/g, and lowest of 1.9 x 10-4cfu/g, while 4.09 x 104 is the average mean. The isolates were identified and characterized using standard microbiological procedures. Staphylococcus aureus was the most prevalent bacterium (26%), Vibro cholera (22%), Shigella (13%) while the least Salmonella has (9%). The Gram positive bacteria (Staphylococcus aureus) were highly susceptible to ciprofloxacin (100 %) and ofloxacin (100 %) but highly resistant to ampicillin (100 %). Gram negative pathogens (Escherichia coli,Vibro cholera and Shigella species) were highly susceptible to perofloxacin (100 %) and Ofloxacin (100 %). It also showed high resistance to amoxicillin (100 %), chloramphenicol (100 %), gentamicin (100 %), nitrofurantoin (100 %). The high prevalence of antibiotic-resistant bacteria in this study is a serious concern as the resistance patterns of E. coli, S. aureus, Salmonella species, Vibro cholerae and Shigella can have implications on human health, thereby suggesting that fish processors and vendors should improve handling hygiene and consumers should also handle fish properly in order to minimize possible health hazards.